Penerapan Model Pembelajaran PBL terhadap Peningkatan Hasil Belajar IPA Kelas VII SMP Islam Al Ula Balikpapan - Henny Faridah; Abd. Haris; Nuraeni Hamzah (Universitas Negeri Makassar, 2024)
This study aims to improve science learning outcomes for class VIII SMP ISLAM AL ULA BALIKPAPAN. This study uses a Problem Based Learning learning model. Data collection techniques were carried out with tests and non-tests, with data collection tools in the form of student activity observation sheets, teacher activity observation sheets, and final test sheets for each cycle. The procedures for implementing this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The Student Activity Observation Sheet technique showed that there was an increase in student learning activities from cycle I to cycle II and from cycle II to cycle III. As for the results of the achievement of the KKM, in the first cycle 50% of students reached the KKM. In the second cycle 68.75% of students reached the KKM, and in the third cycle 83.125% reached the KKM. The results of the research above prove that the Problem Based Learning learning model can improve science learning outcomes for class VIII students of SMP ISLAM AL ULA BALIKPAPAN.